Comparative efficacy and safety analysis of CSE-1034: An open labeled phase III study in community acquired pneumonia - Manu Chaudhary; Shiekh G. Ayub; Mohd A. Mir (Elsevier, 2018)
Objective: CSE-1034 is a novel antibiotic adjuvant entity (AAE) with proven activity against broad range of multi-drug resistant (MDR) pathogens causing various bacterial infections. This phase 3 clinical trial was designed to evaluate the efficacy and safety of CSE-1034 therapy for the treatment of community-acquired pneumonia (CAP) patients of Pneumonia Outcomes Research Team (PORT) risk III-IV. Methods: In this multi-centric, controlled, open-labeled phase 3 trial, adult patients with PORT risk III-IV CAP were randomized to receive either intravenous CSE-1034 (3 g every 12 h) or Ceftriaxone (2 g every 12 h) for 3-10 days. The primary endpoint was clinical response in clinically-evaluable (CE) population and microbiological eradication in microbiologically-evaluable (ME) population at test of cure (TOC) visits. Secondary endpoints included verification of the primary endpoints across all other visits, treatment duration and safety of patients. Results: 156 patients were screened at 5 study centers of which 93 subjects were enrolled in the study and randomized in CSE-1034 and Ceftriaxone treatment arms. In CE population (n = 90), the clinical cure rates at TOC visit were 96% and 64% in CSE-1034 (n = 46) and Ceftriaxone (n = 44) treatment arms respectively (treatment difference: 32.0%; 95% CI, 15.8%-47.1%). The bacterial eradication in ME population of two treatment arms were 94% (n = 36) and 56% (n = 27) at TOC visit (treatment difference: 38.9%; 95% CI, 17.8%-57.6%). Overall, the total number of adverse events (AEs) reported in both groups were 21 (22.5%). The AEs rates reported in two treatment arms were 15.2% in CSE-1034 and 29.8% in Ceftriaxone group. Conclusion: Overall assessment of clinical cure rate, microbiological eradication rate and safety assessment in this study has shown that CSE-1034 is an effective and safe option for the treatment of CAP patients of PORT risk III-IV. Moreover, the superiority of CSE-1034 over Ceftriaxone is also proven. Keywords: CSE-1034, CAP, Ceftriaxone, Anti-microbial resistance